Carnitine levels in patients receiving total parenteral nutrition - Cajaleón F., Lizbeth (2009)
The contribution of lipids in the Total Parental Nutrition (TPN) is given by for long chain fatty acids (LCT) in patients Edgardo Rebagliati Martins Hospital. In the present study compared the plasma levels of carnitine in patients receiving TPN based on long chain and medium chain triacilglicéridos (LCT/MCT) for prolonged time (≥ 7 days). Previously identified carnitine plasma levels in apparently healthy persons and patients with severe hunger and those who receive TPN for more than 20 days. At the end of the study found the following average values of plasma carnitine, expressed in umol / L: 34, 26 for apparently healthy people who are within the normal range, in patients with severe malnutrition (≥ 7 days) 43,27 ; TPN patients based on LCT / TCM (≥ 7 days) 26,68. We found only significant difference when comparing groups based on TPN receiving LCT and TPN-based TCM / TCL (≥ 7 days), p<0.05.